Peran Musik Gerejawi dalam Pembentukan Karakter Anak Usia Dini menurut Perspektif Alkitab - Sjahthi, Herman; Wibowo, Markus (Institut Agama Kristen Negeri Palangka Raya, 2025)
This research examines church music in the formation of early childhood character from a biblical perspective. Through literature studies and analysis of biblical texts, it was found that church music is effective in instilling Christian values ​​such as love, patience, and obedience. Church music also helps children understand the concept of faith and biblical teachings in a way that is easy to remember. This study concludes that church music has the potential to support the development of children's character according to biblical teachings, so that parents and Christian educators are encouraged to integrate it into children's education from an early age.